Preliminary study on association of β2 - adrenergic receptor polymorphism with hypertension in hypertensive subjects attending Balok Health Centre, Kuantan - Atia A.E.; Norsidah K.; Nor Zamzila A.; Rafidah Hanim M.; Samsul D.; Aznan M.A.M.; Rashidah A.R.; Norlelawati A.T. (2024)
Indexed by Scopus